2011
DOI: 10.1561/101.00000045
|View full text |Cite
|
Sign up to set email alerts
|

Using Internet in Stated Preference Surveys: A Review and Comparison of Survey Modes

Abstract: Internet is quickly becoming the survey mode of choice for stated preference (SP) surveys in environmental economics. However, this choice is being made with relatively little consideration of its potential influence on survey results. This paper reviews the theory and emerging evidence of mode effects in the survey methodology and SP literatures, summarizes the findings, and points out implications for Internet SP practice and research. The SP studies that compare Internet with other modes do generally not fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 113 publications
2
67
1
2
Order By: Relevance
“…Regarding content, the questionnaire survey was developed by the researchers in the project and comprised questions aiming to grasp key beliefs and responses to high voltage 1 A review of the use of internet surveys including consumer panel populations and respondents in social and economic research points to both strengths and weaknesses with panels, but conclude that such panels become more and more sound as a basis also for research purposes [39]. Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding content, the questionnaire survey was developed by the researchers in the project and comprised questions aiming to grasp key beliefs and responses to high voltage 1 A review of the use of internet surveys including consumer panel populations and respondents in social and economic research points to both strengths and weaknesses with panels, but conclude that such panels become more and more sound as a basis also for research purposes [39]. Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Yeager et al (2011) reported an effective response rate of 15 % when non-response is included from initial recruitment into the internet panel through to the final survey response. Lindhjem and Navrud (2011b) suggested weighting internet-survey data to account for error introduced by survey non-response. However, Yeager et al (2011) noted that while post-stratification with demographics increases the accuracy, the results are still not comparable to initial random sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Two-thirds of the total number of contacts made (67.8%) did not wish to participate in the survey for different reasons (reported, did not have time, not interested, topic of little relevance, no particular reason). Low response rates in surveys have become a trait of social science research over the past decade or so concurrent with the tremendous increase in internet-based surveys which offer a huge potential for experimentation (Lindhjem and Navrud 2011). Online surveys have also become highly attractive to wildlife research as a cost-effective way to measure constituents' positions on a variety of issues.…”
Section: Sample and Data Collectionmentioning
confidence: 99%